(untitled) (Gragoatá, 2020)
The present paper deals with the polysemous nature of spray/load constructions and clear constructions. The verbs used in these constructions appear in an alternating syntactic pattern: the THM-object variant (e.g. He sprayed paint onto the wall) and the LOC-object variant (e.g. He sprayed the wall with paint). This paper aims to demonstrate that these syntactic alternations are functionally motivated or influenced by topics mentioned in the previous discourse context. ———————————————————————————————- UMA ANÁLISE BASEADA NO USO DE CONSTRUÇÕES SINTÁTICAS ALTERNANTES: O CASO DE CONSTRUÇÕES DE “SPRAY/LOAD” E CONSTRUÇÕES “CLEAR” O presente artigo trata da natureza polissêmica das clear constructions (construções clear) e spray/load constructions (construções spray/load). Os verbos utilizados nessas construções aparecem em um padrão sintático alternante: a variante tema-objeto (p. e.g. He sprayed paint onto the wall) e a variante local-objeto (p. e.g. He sprayed the wall with paint). Este artigo demonstra que esses padrões de alternação sintática são motivados funcionalmente ou influenciados por assuntos mencionados no contexto de discurso prévio. — Original em inglês.